Comparison of Neurologic Event Rates Among HeartMate II, HeartMate 3, and HVAD. Issue 6 (June 2020) - Li, Song; Beckman, Jennifer A.; Cheng, Richard; Ibeh, Chinwe; Creutzfeldt, Claire J.; Bjelkengren, Jason; Herrington, Joni; Stempien-Otero, April; Lin, Shin; Levy, Wayne C.; Fishbein, Daniel; Koomalsingh, Kevin J.; et al.
Abstract : Strokes remain a leading cause of morbidity and mortality in patients with ventricular assist devices (VADs). Varying study populations, event definitions, and reporting methods make direct comparison of neurologic event risk across clinical trials and registries challenging. We aim to highlight important differences among major VAD studies and standardize rates of neurologic events to facilitate a comprehensive and objective comparison. We systematically identified and analyzed key clinical trials and registries evaluating the HeartMate II (HMII), HeartMate 3 (HM3), and HVAD devices. Reported neurologic events were nonexclusively categorized into ischemic stroke, hemorrhagic stroke, disabling stroke, fatal stroke, and other neurologic events per the studies' definitions. Event rates were standardized to events per patient-year (EPPY) and freedom from event formats. Seven key clinical trials and registries were included in our analysis. There is significant variation and overlap in neurologic event rates for the three VAD platforms across clinical trials (all neurologic events [EPPY]: HM3 0.17–0.21; HMII 0.19–0.26; HVAD 0.16–0.28). None performs consistently better for all types of neurologic events. Furthermore, stroke rates among VAD trials correlated with baseline stroke risk factors including ischemic etiology, history of atrial fibrillation, and history of prior stroke.